Dodging the devil : letters from the front - Martindale, George (Hardie Grant, 2016)
Landing on the Gallipoli Peninsula at Anzac Cove on 25 April 1915, fighting at Lone Pine, surviving Fromelles and suffering Bullecourt, George Martindale's war experiences reflect a litany of our nation's hallowed trials. George described these actions for members of his family in the letters he sent home, forming a collection of his writings that is the basis of this book. He may well have become one of the great writers of twentieth century Australia had his life not ended prematurely as a result of the injuries he sustained on the Western Front. George's letters were a gift to his family but more so to posterity. They retain the scent of the trenches, and the stains of no man's land. In them he honoured his mates, cherished his heritage and condemned falsities. His letters allow us to look back more than 100 years, and for his words to reach out to future generations.